Gestão e gerenciamento de resíduos de serviço de saúde dos grupos “A”, “B” e “E” no estado de Goiás - Ariza, Bernardo Guedes (2015)
The growing generation of Health Services Waste is made by one of the great environmental preoccupations of the humanity. After the promulgation of the law 12305 in the August 02 of 2010 that established the National Politics of the Solid Residues, the theme solid residues gained distinction in national level. Health Services Waste, for definition, is the resultant residue of activities of unities of health that, for his characteristics, need processes differentiated in the handling, demanding or prior non-treatment for the final arrangement. The diagnosis of the current situation of the Health Services Waste attests with the preparation of policies that attend the demand of recuperation, treatment and final arrangement of these residues. The unsuitable handling of the Health Services Waste can be the cause of situations of risk, what in the alert on the necessity of the management being diagnosed in Goiás. In this way, in visit to establishments of health (pharmacy, odontologic clinic, veterinary clinic, basic unity of health and general hospital) in 6 local authorities from Goiás (Piranhas, Rubiataba, Santa Helena de Goiás, Goianésia, Luziânia and Goiânia), representing different population belts, it happened quantitativamente and qualitatively the Health Services Waste of the groups A, B and E produced in Goiás. In each establishment, the Health Services Waste were segregated and weighed. The hospitals, bigger creators of Health Services Waste, produce, on average, 1,76 Kg of Health Services Waste for bed occupied one service day. In Brazil, these values vary from 1,2 to 3,5 kg/bed.day. Regarding final destination, the incineration is the technology chosen by 76 % of the local authorities from Goiás for the destination of the RSS produced in public establishments of health. Meantime, the most viable alternative for the destination of the Health Services Waste, considering the reality from Goiás, is at disposal of the RSS of the groups A and E together with the municipal solid waste in joined sanitary landfills. For the destination of the Health Services Waste of group B, the most viable alternative is the incineration.